(3GdGNJjGQGJ GdfLhejIs - (3GdQGRjs
(3ChdgG (B:s
(3GdMeO dgd efTF GdbWQ , heSOO GdacQ CeG HYO , agPg LedI eNJUQI ai GdGNJjGQGJ , aEf GdMGLI QHeG OYJ Edi GdeYGdLI , hcGf GdJCfi ai GdCehQ Edi MUhd GdENJjGQ GdcGed s
(3BNQgG (B:s
(3hjSJMH dYH GdJQO hGdTWQfL ai SGYI GdRgQI , hjcQg chfg ai HGbi GdHQhL , hGJUGdg HRMd , hGdCLhO Cf jLdS GdHGOi ai GdLgg GdJi jchf ajgG GdbeQ ef GdCab , agPg LedI eNJUQI eYhd YdjgG ai eYGdLI GdCeQ , hGddg CYde , hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde eged GdfbW cKjQkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3Gdadcs